PENINGKATAN KETERAMPILAN DESAIN DIGITAL SISWA SMK PANTI KARYA 3 MELALUI PELATIHAN PEMBUATAN PRESENTASI DAN INFOGRAFIS DENGAN VENNGAGGE - Siswopranoto, Agung; Chairyansyah, Syafril (KOMMAS: Jurnal Pengabdian Kepada Masyarakat, 2026)
Data visualization and digital design skills have become crucial competencies in the Industry 4.0 era; however, many vocational high school (SMK) students are still limited to using conventional presentation software without considering aesthetic principles and information clarity. This Community Service (PKM) program aims to enhance the digital design skills of students at SMK Panti Karya 3 through training in creating presentations and infographics using the Venngage platform. The implementation method consisted of three stages: 1) Preparation (needs analysis and coordination), 2) Implementation (workshops on design theory, typography, color psychology, and hands-on practice using Venngage), and 3) Evaluation. The participants of this program were students of SMK Panti Karya 3 selected through purposive sampling. The results of the activity indicate a significant improvement in the students' digital competence. Based on pre-test and post-test results, there was a 75% increase in the average score of design principle comprehension. Technically, 90% of the students were able to transform textual data into communicative and visually appealing infographics. The evaluation of the final products showed that using Venngage effectively assisted students in organizing professional layouts without requiring complex graphic design expertise. In conclusion, this program successfully enhanced the students' visual literacy and confidence in producing competitive digital content.